Essays in applied microeconomics - Pedemonte, S (2019)
This thesis is made of three chapters. In Chapter 1 I investigate some of the potential effects of the interaction between minimum wages and job frictions on labour market outcomes in the UK. In a random search model with wage-posting and productivity dispersion across firms, under certain conditions, an increase in the minimum wage has stronger effects on separations between firms and workers facing relatively higher frictions than on separations between firms and workers facing relatively lower frictions. In this chapter, I test this prediction within two separate empirical settings, using two sources of UK data. I find some evidence that employment transitions of "high-friction" workers respond more strongly relative to the "low-friction" group’s. In Chapter 2 I analyse voting behaviour of US House Democrats on two separate bills aimed at permanently repealing or reforming the estate tax. Existing analyses of politicians’ voting behaviour are consistent with a framework in which voting decisions result from the competing influences of politicians’ own ideology and interests, special interests, and the interests of their constituents. Recent analyses of roll-call votes in the US Congress suggest that local interests are more likely to influence political decisions when the issues at hand are prominent and when the stakes associated with them are clear. Making use of data on representatives’ wealth and personal characteristics, I am able to assess whether their private interests influence their voting behaviour. Further, I use data on campaign contributions and advertising, characteristics of electoral constituents, and measures of politicians’ ideology. My results confirm the predictive power of ideology and campaign contributions found elsewhere in the literature. I am not able to find clear evidence that local interests had an influence on voting behaviour. Finally, I find no evidence that politicians’ own wealth had an influence on their voting behaviour. Chapter 3 is co-authored with Brian Bell and John Van Reenen. In this paper, we investigate whether moving to relative performance contracts has improved the alignment between CEO pay and performance. To address this, we use an original dataset on CEO contracts for almost 500 publicly listed UK companies. We find that pay responds more strongly to increases in firm performance than to decreases, and that this asymmetry is present only in weakly governed firms. Further, we find that CEO pay is still linked to positive random industry shocks. This result is due to the fact that failing awards in weakly governed firms are redesigned in ways that reduce the risks attached to them for the CEOs. These findings suggest that reforms to the formal structure of CEO pay contracts are unlikely to align incentives in the absence of strong shareholder governance.